Zakat Management Practices and Sustainable Development in Indonesia - Erni, Erni; Artis, Artis; Rahman, Rahman (Yayasan Sinergi Kawula Muda, 2024)
This study examines how Zakat management practices in Indonesia relate to sustainable development, with an emphasis on institutional capacity, transparency, efficiency of Zakat collection, and the effectiveness of distribution. A numerical method, using Structural Equation Modelling with Partial Least Squares (SEM-PLS), was used to examine data gathered from a group of 170 people. Analysed were descriptive statistics, evaluations of measurement models, and examinations of structural models to investigate how essential factors interact. The findings showed strong and important connections between institutional capacity, transparency, efficiency of Zakat collection, and efficacy of distribution and sustainable development results. The research offers practical advice for Zakat organisations and policymakers to improve their methods, highlighting the important role of transparency and efficient distribution in increasing socio-economic benefits.